Gram Stain and Ziehl Neelsen Stain: Limited but Important, Specific Diagnostic Tool - Lutfor, Afzalunnessa Binte (Bangladesh Journal of Medical Microbiology, 2017)
Abstract not available Bangladesh J Med Microbiol 2017; 11 (2): 1-4